2016
DOI: 10.1245/s10434-016-5509-4
|View full text |Cite
|
Sign up to set email alerts
|

Rationale for a Minimum Number of Lymph Nodes Removed with Non-Small Cell Lung Cancer Resection: Correlating the Number of Nodes Removed with Survival in 98,970 Patients

Abstract: Survival of early-stage NSCLC patients is associated with the number of LNs removed. The surgical management of early-stage NSCLC should include thoracic lymphadenectomy of at least 10 nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
53
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(63 citation statements)
references
References 34 publications
8
53
2
Order By: Relevance
“…Lymph nodes metastasis status was a strong predictor of both local control and OS for patients with NSCLC . The previous study in our institution has revealed that patients with pathologic single station N2 diseases could get favorable survival outcomes from upfront surgery followed by adjuvant therapy .…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Lymph nodes metastasis status was a strong predictor of both local control and OS for patients with NSCLC . The previous study in our institution has revealed that patients with pathologic single station N2 diseases could get favorable survival outcomes from upfront surgery followed by adjuvant therapy .…”
Section: Discussionmentioning
confidence: 87%
“…In 576 patients, 403 recurrence events were observed, in which distant recurrence accounted for 70% (282 events). The failure pattern was a major reason why no OS or RFS improvement was observed in IIIA-N2 cohort.Lymph nodes metastasis status was a strong predictor of both local control and OS for patients with NSCLC [22][23][24]. The previous study in our institution has revealed that patients with pathologic single station N2 diseases could get favorable survival outcomesF I G U R E 4 Kaplan-Meier survival curves of matched patients with different adenocarcinoma subtypes who received POCT.…”
mentioning
confidence: 89%
“…The NCDB captures treatment and outcomes data for 70% of new cancer diagnoses in the United States, serving as a valuable resource for researchers as well as those interested in quality control . Similar investigations have utilized the NCDB to report on survival after various forms of treatment in many malignancies . However, the NCDB has not been previously utilized to investigate the overall survival associated with various methods of local control in patients with Ewing's sarcoma.…”
Section: Introductionmentioning
confidence: 99%
“…The benefit of thorough thoracic lymphadenectomy in early-stage NSCLC was further emphasized with multiple metaanalysis and population-based studies demonstrating improved OS when greater numbers of lymph nodes were resected and examined. [104][105][106][107][108] Adjuvant Therapy in Completely Resected NSCLC Section Authors: Heather Wakelee, MD, and Yi-Long Wu, MD…”
Section: Tnm Staging Systemmentioning
confidence: 99%